Shadow Kingdom: Lotharingia and the Frankish World, C.850–C.1050. Issue 6 (10th June 2013) - MacLean, Simon
Abstract The lost realm of Lotharingia presents an excellent case‐study with which to explore the last years of the Carolingian Empire in the ninth century and the emergence of its successor kingdoms in the tenth. Following the political history of the kingdom from its creation in the reign of King Lothar II (855–69) through the end of the empire in 888 and across the conflict‐ridden map of tenth‐century Europe reveals some of the key dynamics of the post‐Carolingian world. These dynamics have long been the subject of debates between scholars and have also played a part in the grand narratives of modern European nations whose roots have been located in the ninth and tenth centuries. Lotharingia represents an interesting and unusual case, since its independent existence was fleeting, but it somehow left behind a distinctive shadow that continually resurfaced in between the proto‐French and ‐German kingdoms on either side. A discussion of questions of authority and identity in Lotharingia, which was an obviously artificial creation of Carolingian politics, and which had no long‐term future as a nation‐state, allows us to strip away some of the baggage carried by modern national historiographies and ask what was specific about this important phase in the history of European state‐formation.